KADAR PLUMBUM (PB) DALAM UMBI BAWANG MERAH DI KECAMATAN KERSANA KABUPATEN BREBES - Eko Hartini (Dian Nuswantoro Semarang, 2011)
Background: The Agro-chemical materials use (fertilizers and pesticides) to increase red onion production in Brebes is inevitable. Generally, farmers in that area using a pesticide by mixing 3-5 types of pesticides and by frequency of spraying almost every day. In its growth, red onion plants absorb nutrients from the soil, including heavy metal such as PB, so that the product or agricultural products may contain heavy metal.Methods: This is a Descriptive Observational research with survey method and using Cross Sectional approach. This research was conducted in three selected villages in Kersana Subdistrict in Brebes namely Kemukten, Limbangan and Sutamaja Village, by considering thehighest level of pesticide usage compared to other villages (Department of Agriculture and Kersana Sub-district Office data). Lead (Pb) level analysis in red onion bulbs was conducted using Atomic Absorption Spectrometry (AAS).Results: Pesticides used by farmers in Kersana Sub-district in Brebes District are Antracol 70 WP, Buldok 25 EC and Dithane M-45 and also which contain active ingredients such as Propineb 70 %, Mankozeb and Profenofos known to contain Pb and contamination of Pb residues in red onion bulbs and has approached critical threshold which are 0,16 – 0,20 mg/kg.Keywords: Plumbum (Pb) Concentration, onion